Antimicrobial Consumption and Resistance in a Tertiary Care Hospital in Jordan: Results of an Internet-Based Global Point Prevalence Survey - Khawla Abu Hammour; Esraa AL-Heyari; Aya Allan; Ann Versporten; Herman Goossens; Ghayda' Abu Hammour; Qusai Manaseer (MDPI AG, 2020)
Background: The Global Point Prevalence Survey (Global-PPS) provides a standardised method to conduct surveillance of antimicrobial prescribing and resistance at hospital level. The aim of the present study was to assess antimicrobial consumption and resistance in a Jordan teaching hospital as part of the Global-PPS network. Methods: Detailed antimicrobial prescription data were collected according to the Global Point Prevalence Survey protocol. The internet-based survey included all inpatients present at 8:00 am on a specific day in June-July 2018. Resistance data were based on microbiological results available on the day of the PPS. Results: Data were collected for 380 patients admitted to adult wards, 72 admitted children, and 36 admitted neonates. The overall prevalence of antimicrobial use in adult, paediatric, and neonatal wards was 45.3%, 30.6%, and 22.2% respectively. Overall, 36 patients (7.4%) were treated for at least one healthcare-associated infection (HAI). The most frequent reason for antimicrobial treatment was pneumonia. Cephalosporins and carbapenems were most frequent prescribed among adult (50.6%) and paediatric/neonatal wards (39.6%). Overall resistance rates among patients treated for a community or healthcare-associated infection was high (26.0%). Analysis of antibiotic quality indicators by activity revealed good adherence to treatment guidelines but poor documentation of the reason for prescription and a stop/review date in the notes. Conclusion: The present study has established baseline data in a teaching hospital regarding the quantity and quality of prescribed antibiotics in the hospital. The study should encourage the establishment of tailor-made antimicrobial stewardship interventions and support educational programs to enhance appropriate antibiotic prescribing.